Students' cognitive styles: Algebraic function derivative problem solving profiles - Beela, Cilint Rosa; Hasbi, Muh; Rizal, Muh; Nasir, Rahma (Universitas Islam Negeri Raden Intan Lampung, 2025)
Cognitive style is one of the factors that affect the way individuals understand, process, and solve problems. The purpose of this study is to obtain an overview of students who have Field Dependent (FD) and Field Independent (FI) cognitive styles in solving algebraic function derivative problems. This type of research is descriptive research with a qualitative approach. The results of the study show that there are differences in FD and FI subjects in solving problems of derivative algebraic functions. FD and FI subjects can identify information from the problem in full and formulate and construct mathematical models based on the information and reasoning made, but FD subjects do not provide reasons for spelling. The FD subject did not use the settlement strategy correctly, and in the settlement process there were still procedural errors such as errors in performing algebraic manipulation, writing the mark of the calculation operation, and the differentiation process, so that the stationary point and the maximum volume of the aquarium were not correct, while the FI subject used the settlement strategy with the correct steps and calculations so that it succeeded in obtaining the maximum volume of the aquarium. Although it has not been able to prove that the stationary point obtained is the maximum value. FD and FI subjects were able to conclude the results of the settlement orally, but the FD subjects did not write the conclusions on the answer sheet. FI subjects rechecked the answers, while FD subjects did not recheck. FD subjects tend to be less thorough in solving problems derivative from algebraic functions and less reflective in examining the results of the solution, while FI subjects show independence, precision, and the ability to formulate solving steps so that they can successfully obtain the right answers.